Volvariella griseoalba (Agaricales, Volvariellaceae), a new species from Punjab, Pakistan - Arshad, Wasiqa; Ijaz, Hira; Khan, Mehboobullah; Yasmeen, Aneela; Zhao, Chang-Lin; Ghafoor, Aneeqa; Komal, Eisha; Niazi, Abdul Rahman; Jabeen, Sana (Phytotaxa, 2024)
Volvariella griseoalba is described as a new species from Punjab, Pakistan. The species was separated from its morphologically closest relative, V. sathei by its shiny greyish-white, umbonate pileus, subglobose to broadly ellipsoid basidiospores, utriform cheilocystidia and a white to brown volva. Molecular phylogenetic analyses of ITS and LSU region of the nrDNA also supported the studied taxon as a distinct species in Volvariella.